Evaluación docente para una mejora continua en el cantón La mana - Toapanta Cayo, Marco Rolando (2019)
When looking for excellence in educational performance it is essential to continuously evaluate the procedures of educational management teaching, with the purpose of offering a quality education, warmth and satisfy the expectations of the educational community, with this perspective was developed the research theme "Teaching evaluation for a continuous improvement in La Mana canton" in order to achieve this, it is proposed as an investigative objective to define the evaluation of teachers of Basic Education in La Mana canton, Province of Cotopaxi in the academic year 2016-2017 and specify the profile of the teacher to achieve continuous personal and institutional improvement. In order to fulfill the objective, field research was carried out with the application of the survey to the teachers of the Educational Units of the Canton of La Mana, using the theoretical development of the formative and field research as well as the inductive- deductive. As for the direct beneficiaries were of the project to investigate were a total of 458 teachers belonging to the district of Canton La Mana. Through the investigative process it was concluded that the teacher evaluation carried out by the MINISTRY OF EDUCATION, which allowed to detect failures and successes in the pedagogical processes, besides that at the level of the teachers of Basic Education they fulfill the profiles suitable for a quality education.